“Arresting Gaddafi Will Be the Most Effective Way to Stop these Rapes”. Sexual Violence in the Western Media’s Coverage of the War in Libya - Garraio, Júlia (2012)
The aim of the present article is to tackle the way in which CNN and BBC – as leading examples of hegemonic Western media – represented the cases of sexual violence that were being denounced during the war in Libya. Looking into the coverage of this war may be useful to analyze the very concept of wartime rape and enquire to which extent rape narratives are framed by social constructs of sexuality, gender, and race, as well as by political agendas. I argue that the Western media tended to pay more attention to rape stories that were politically beneficial to NATO’s war effort in support of the opposition, and showed less interest in accusations that did not involve Gaddafi's henchmen. I finally discuss the culturalization of sexual violence, by addressing the strategies of othering implied in the media explanations and contextualization of the rapes.